Analysis of Thermo-elastohydrodynamic Lubrication Characteristic of the Internal Meshing Gear Transmission System - Qingqing Zhu; Qiang Sun; Yuanyuan Li; Juan Song; Guangxiao Jian (Jixie chuandong)
In order to find out the thermo-elastohydrodynamic lubrication characteristic of internal meshing gear transmission，considering the influence of various gear transmission types and different modification coefficients，an elastohydrodynamic lubrication model for the internal meshing gear transmission is established to analyze the thermo-elastohydrodynamic lubricating characteristics of internal meshing gear system. The research shows that compared with other transmission types，for the modified internal meshing gear system，when the positive transmission is realized，the lubrication effect of the gear system is the best，the thick lubricating oil film can be formed between the meshing gear teeth，the friction coefficient between the gear teeth and the highest temperature rise of the oil film are the least，and the thermal adhesive bearing capacity is the strongest. When positive transmission is realized，appropriate increment of the modification coefficient can further improve the lubrication characteristics of the tooth surface，but at the same time reduce the oil film stiffness.